Permanências setecentistas?: o público e o privado no Vale dos Contos de Ouro Preto - Karolyna de Paula Koppke (2017)
This dissertation aims to study the relations between the public and the private spheres in the Vale dos Contos, located in the city of Ouro Preto, state of Minas Gerais, Brazil. It is the center of an urban block, for which are turned the backs of the lots still established in the 18th century. We start in this century, when the Vale is conformed as a residual urban area, and reach the beginnings of the 21st century, when a municipal urban park is inaugurated in there, implanted within the framework of the Monumenta Program. It is questioned if traces of what characterized the public and the private on the 18th century still survive in the Vale dos Contos, whether in the field of material or behaviour. If they resist, we aim to know in which ways the implanted project is dealing with them. In order to answer those questions, a descriptive table of the conflicts and agreements associated with the park will be constructed in the first chapter. This description results from the cataloging and analysis of documentation collected from the bodies responsible for the project and its execution, as well as interviews with key agents of these processes. The second chapter aims to reconstruct the Vale dos Contos project historically, since its conception in the 1960s by the Portuguese urbanist Viana de Lima until the proposal conceived by the Spanish urbanist Eduardo Villaescusa, three decades later. Finally, the third chapter reconstitutes, through theoretical contributions from the fields of Urban Morphology and Law, on the one hand, and History, Sociology and Anthropology, on the other, the panorama of the public and private spheres in the 18th century. Next, it presents the fieldwork done in the Vales perimeter buildings, which included the visit and identification of the traces of that century in 12 of the 75 properties located there. From this research, it was verified the necessity of intervention in the Vale dos Contos peripheral backyards as a condition for the new urban equipment full operation. The study of this theme contributes to the reflection about interventions of the same genre in other cities that inherited the traditional Portuguese urbanism